TECHNOLOGY OF DEVELOPING REFLECTIVE CULTURE IN UROLOGIST-PHYSICIANS WITHIN AN INNOVATIVE EDUCATIONAL ENVIRONMENT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This article examines technology-driven approaches to cultivating reflective culture among urologist-physicians in innovative educational environments. Using structured pedagogical frameworks and simulation-based methods, the research evaluates measurable shifts in professional self-assessment, clinical decision-making, and continuous learning behavior among urology residents undergoing competency-based training programs over a 12-month observational period.